2017
DOI: 10.2214/ajr.16.17124
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Appearance and Clinical Impact of Preoperative Breast MRI in Pregnancy-Associated Breast Cancer

Abstract: Breast MRI had a high sensitivity for PABC in our study population. MRI may play an important role in PABC because it changed the surgical management of 28% of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 26 publications
0
13
0
8
Order By: Relevance
“…Experience with MRI in pregnancy is limited and gadolinium‐enhanced contrast is contraindicated in the first trimester because it crosses the placenta. A recent study of breast MRI showed 98% sensitivity in diagnosis of pregnancy‐associated breast cancer and changed treatment modality in 28% of women . Comprehensive staging studies are needed because breast cancer in pregnancy may present in advanced stage.…”
Section: Specific Cancersmentioning
confidence: 99%
“…Experience with MRI in pregnancy is limited and gadolinium‐enhanced contrast is contraindicated in the first trimester because it crosses the placenta. A recent study of breast MRI showed 98% sensitivity in diagnosis of pregnancy‐associated breast cancer and changed treatment modality in 28% of women . Comprehensive staging studies are needed because breast cancer in pregnancy may present in advanced stage.…”
Section: Specific Cancersmentioning
confidence: 99%
“…Detection rates of PABC are very high using mammography, ultrasonography (US) or magnetic resonance (MRI) being 91%, 100% and 97%, respectively, according to Myers et al [13].…”
Section: Diagnostic Imagingmentioning
confidence: 99%
“…Breast MRI has a sensitivity of 98% [13]. Contrastenhanced MRI is not recommended during the first trimester of pregnancy because the contrast agent used, gadolinium, is classified as pregnancy category C. Gadolinium-based contrast media cross the placenta in measurable quantities and can be identified in the amniotic fluid [22].…”
Section: Diagnostic Imagingmentioning
confidence: 99%
“…Pregnancy-associated breast cancer (PABC) is determined as a breast malignancy identified for women during pregnancy or within the first twelve postpartum months (1,2). Some evidence suggests that it is worthwhile to differentiate between diagnosis during pregnancy and diagnosis during the postpartum phase (18) because separating patients in this way reveals a potential prognostic difference between the two groups.…”
Section: Introductionmentioning
confidence: 99%